Retrospective study of the efficacy of methylprednisolone vs. triamcinolone in lumbar epidural steroid injections for the treatment of low back pain due to degenerative disc disease - Higgins, Zachary R.; Garg, Shuchita; Burroughs, Timothy; Qualls, Katherine A.; Zhang, Jun-Ming; Strong, Judith A. (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
Objective A common low back pain treatment is epidural injection of corticosteroids. The nominal target of anti-inflammatory corticosteroid drugs is the glucocorticoid receptor (GR). In vitro studies show many clinically used steroids also activate the mineralocorticoid receptor (MR) with substantial potency. Based on preclinical studies, this may have pro-inflammatory and pro-nociceptive effects that counter the desired GR effects. Of two outpatient pain clinics associated with the University of Cincinnati Department of Anesthesiology, one primarily used methylprednisolone while the other used mainly triamcinolone for epidural steroid injections. We hypothesized that triamcinolone would give better outcomes because in vitro, ratio of MR/GR potency is about 10 fold less favorable for methylprednisolone. Methods We conducted a retrospective chart review of adults receiving lumbar epidural steroid injection for low back pain due to degenerative disc disease at the two pain clinics. For subjects treated at the first clinic, we obtained basic demographics, smoking history, 2 primary outcomes (patient-rated percent improvement in pain levels, and injection outcome rated as poor, partial, or good), and pain ratings (0–10 scale) before and after injection. For analysis, a subset of subjects from the second clinic was matched as closely as possible (sex, age, race, and ethnicity) to those from the first clinic. Results Eighty-six subjects from the first clinic were identified, of whom fifty-five met inclusion criteria. Review of 83 potentially matched subjects from the second clinic yielded 37 subjects. From this combined set of subjects, 44 receiving triamcinolone and 48 receiving methylprednisolone were obtained. Matching was effective in avoiding significant differences between the two drug groups in age, weight, sex, race, and body mass index, however, the incidence of smoking (current and former) was significantly higher in the methylprednisolone group (who were primarily from clinic 1). The injection responses codified on a 0–2 scale, where 0 indicated a poor response, 1 a partial response with a second injection recommended, and 2 a good response where no further treatment was recommended at the 1 month follow up point, were not significantly different between the groups (Mann–Whitney, p = 0.44) although the triamcinolone group overall had slightly better responses. However, the patient-reported percent improvement after the injection was significantly better for the triamcinolone than for methylprednisolone (60% ± 5.3 vs. 42% ± 4.9), as was the pain ratings (0–10 scale) after the injection (5.0 ± 0.5 vs. 6.3 ± 0.3). A marked demographic difference between the two clinics in smoking rates was not controlled for in subject matching but accounting for smoking status did not affect the observed differences between the two steroids. Conclusions Differences in the two primary outcomes, patient-reported percent improvement and pain ratings after epidural steroid injection, were consistent with the hypothesis that more GR-selective steroids may give better outcomes though the differences were modest. We propose that one factor in choosing steroids should be their relative potency in also activating the pro-inflammatory mineralocorticoid receptor. Graphical Abstract